2018
DOI: 10.1186/s12970-018-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of female and male vegetarian and vegan endurance runners compared to omnivores – results from the NURMI study (step 2)

Abstract: BackgroundHealth-related effects of a vegetarian or vegan diet are known to support parameters positively affecting exercise performance in athletes, whereas knowledge about psyche and wellbeing is sparse. Therefore, the aim of the Nutrition and Running High Mileage (NURMI) Study (Step 2) was to compare Quality of Life (QOL) scores among endurance runners following a vegetarian or vegan diet against those who adhere to an omnivorous diet.MethodsThe study was conducted following a cross-sectional design. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 70 publications
2
64
0
6
Order By: Relevance
“…Secondary outcomes (Table 3) Ten of the 18 studies examined the secondary outcomes of self-harm, mood, stress perception, affective well-being, and QoL (Table 3). In contrast to the clear results on depression and anxiety, three studies found no differences between groups (Boldt et al 2018;Pfeiler and Egloff 2018;Wirnitzer et al 2018), three favored meat-abstainers (Beezhold et al 2015; Beezhold and Johnston 2012; Beezhold, Johnston, and Daigle 2010), three studies favored meat-consumers (Baines, Powers, and Brown 2007;Neumark-Sztainer et al 1997;Perry et al 2001), and one study provided mixed results (Lavallee et al 2019).…”
Section: Summary Of Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Secondary outcomes (Table 3) Ten of the 18 studies examined the secondary outcomes of self-harm, mood, stress perception, affective well-being, and QoL (Table 3). In contrast to the clear results on depression and anxiety, three studies found no differences between groups (Boldt et al 2018;Pfeiler and Egloff 2018;Wirnitzer et al 2018), three favored meat-abstainers (Beezhold et al 2015; Beezhold and Johnston 2012; Beezhold, Johnston, and Daigle 2010), three studies favored meat-consumers (Baines, Powers, and Brown 2007;Neumark-Sztainer et al 1997;Perry et al 2001), and one study provided mixed results (Lavallee et al 2019).…”
Section: Summary Of Resultsmentioning
confidence: 91%
“…Two studies examined well-being and QoL (Boldt et al 2018;Pfeiler and Egloff 2018). In a sample of 281 endurance runners (57% female), Boldt et al (2018) found that QoL did not differ between groups (Boldt et al 2018).…”
Section: Well-being and Qolmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, such data form the basis for assessing the relationship of a plant-based diet with the body composition, the antioxidant and immunological capacity and, ultimately, with the health and performance of athletes [24,26,27]. Present studies investigating the relationship between a vegetarian and VEG diet and exercise do not differentiate between vegetarians and VEG [26], are outdated [28], questionnaire-based [25,29,30] or do not contain nutritional assessment including biochemical markers [31,32].…”
Section: Introductionmentioning
confidence: 99%